My Father, Daniel Boone : The Draper Interviews with Nathan Boone - Boone, Nathan, 1781-1856 (Book collections on Project MUSE., 1999)
My Father, Daniel Boone is an engaging account of one of America's great pioneers, in which Nathan makes a point of separating fact from fiction. From explaining the methods his father used to track game to detailing how land speculation and legal problems from title claims caused Boone to leave Kentucky and take up residence farther west, Nathan Boone's portrait of his father brings a crucial period in frontier history to life.